Immunological Changes in Monocyte Subsets and Their Association With Foxp3+ Regulatory T Cells in HIV-1-Infected Individuals With Syphilis: A Brief Research Report - Guo, Na; Liu, Lifeng; Yang, Xiaodong; Song, Ting; Li, Guanxin; Li, Li; Jiang, Taiyi; Gao, Yanqing; Zhang, Tong; Su, Bin; Wu, Hao (Frontiers in Immunology, 2019)
The incidence of syphilis has increased dramatically in men who have sex with men (MSM), especially those with HIV-1 infection. Treponema pallidum and HIV-1 are bidirectionally synergistic, accelerating disease progression reciprocally in co-infected individuals. We have shown that monocytes have different effects on T helper cells at different stages of HIV-1 infection. However, the immunological changes in the three monocyte subsets and in regulatory T cells (Tregs), and the associations between these cell types during syphilis infection among HIV-1-infected MSM remain unclear. Herein, we used cell staining methods to explore changes in monocyte subsets and Tregs and any associations between these cells. We found that the frequency of classical monocytes was higher in the rapid plasma reagin (RPR+) group than in the healthy controls (HCs) and the chronic HIV-1 infection (CHI) plus RPR+ (CHI&RPR+) group. The frequencies of Foxp3+CD25+CD45RA+ and Foxp3+Helios+CD45RA+ Tregs were significantly higher in the RPR+, CHI, and CHI&RPR+ groups than in HCs, whereas the frequency of CD45RA+ Tregs was lower in the CHI&RPR+ group than in CHI group. The frequencies of Foxp3+CD25+CD45RO+ and Foxp3+Helios+CD45RO+ Tregs were lower in the RPR+, CHI, and CHI&RPR+ groups than in HCs. The frequency of intermediate monocytes was inversely correlated with the frequency of CD45RA+ Tregs and positively correlated with the frequency of CD45RO+ Tregs. These results demonstrate for the first time that intermediate monocytes control the differentiation of Treg subsets in Treponema Pallidum/HIV-1 co-infections. These findings provide new insights into an immunological mechanism involving monocytes/Tregs in HIV-infected individuals with syphilis.